Redesign Website Puskesmas Pasundan Menggunakan Metode Design Thinking - Ananda Putri Anugra Hariska; Noor Alam Hadiwijaya; Damar Nurcahyono (JURNAL VOKASI TEKNIK, 2026)
This study aims to design a prototype of Online Referral at Puskesmas Pasundan that is easy to use by users, using the Design Thinking method. The stages carried out include Empathize, Define, Ideat, Prototype and Test. The prototype produced to add features with a display similar to the original appearance of the Puskesmas Pasundan website, by adding the Puskesmas logo on the landing page. The results of this study confirm the user-centered approach and increase user convenience.